PENDIDIKAN AGAMA DAN KONSTRUKSI GENDER DALAM MASYARAKAT ISLAM - Husni Abdulah Pakarti, Muhammad; Hendriana, Hendriana; Farid, Diana; Ulpah, Ghina; Afifah, Nurul (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
Gender construction in Islamic societies was influenced by religious interpretations and local culture, which can affect social roles and expectations for individuals based on gender. This research aims to analyze the interaction between Islamic religious education and gender construction in Islamic society context. This research uses a qualitative method with a literature study approach or literature analysis to collect and criticize literature related to religious education, gender, and Islam. After the data is collected, it is analyzed to produce concrete conclusions. The research findings indicate that religious education has a significant role in maintaining and changing gender construction in Islamic society. The interpretation of religion and its emphasis in the religious education curriculum can influence how gender roles are defined and implemented daily. In addition, cultural factors and social context also play a role in shaping gender construction in Islamic societies. Local traditions, social norms, and historical factors can reinforce or change perceptions of gender roles in society. The research also highlights the importance of religious education in reflecting on Islamic teachings to promote gender equality and overcome patriarchal views. This research was expected to provide further insights into how Islamic religious education can influence the construction of gender in Islamic societie